Dance as a socio-political tool: The historical developments into contemporary dancing diplomacy and the Portuguese testimony - Costa, Beatriz Sá (2024)
This master dissertation intends to explore the intersection of cultural diplomacy and dance, considering its ability to coerce, influence and impact international relations. Dance is a sui generis art form and has been historically used as a powerful instrument that not only is relevant for artistic expressions and cultural sharing but also as a soft power tool in cultural diplomacy. As such, dance can wisely be a tool for different purposes in foreign affairs due to its holistic dimension. This field of research emerged as a vital way to increasingly promote cultural understanding, empathy, and respect by empowering communicative environments between nations. Through the analysis of some the historical international examples, especially inherent to the Cold War period but not exclusively, its intended to create a robust base for the study of dance in cultural diplomacy. This enables an understanding of its impacts and capabilities to specify for the analysis of dance as soft power tool in Portuguese cultural diplomacy. As primary examples, Ballet Verde Gaio, Ballet Gulbenkian and the National Ballet of Portugal, have shown to display the ability to reinforce Portuguese cultural identity and establish its presence in the international arena. Despite the evidence of this practice in Portugal, dance diplomacy is still a very underexplored field of research, and this study also intends to evoque the urgence for that more positive transition.